PENGARUH GAYA KEPEMIMPINAN, INSENTIF DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI SATKER SEKRETARIAT KEMENTERIAN PEMBANGUNAN DAERAH TERTINGGAL - Grace Meyanti Putri, - (2014)
Relationship Leadership Style, Incentives and Work Environment Against Employee Performance on The Secretariat of the Ministry of Rural Development. Development of disadvantaged areas is a planned effort to transform an area that is inhabited by a community with a wide range of socio-economic problems and physical limitations; advanced into the area with the community quality of life is the same or not far behind compared to other Indonesian society. The purpose of this study was to determine whether there is a relationship style of leadership, incentives and work environment either partially or simultaneously on the performance of employees in the Secretariat of the Ministry of Rural Development The population in this study are all servants as much as 135 people , while the study sample as many as 58 samples. The data required in this study is covering the primary and secondary data, which is then analyzed using the software Statistical Product and Service Solutions. The research results are as follows : a. Partially a significant correlation between leadership styles on employee performance, where the hypothesis test showed that t = 5.242 > t ,abl-.,; = 2.303 . R = 0. 570 and R2 = 0.325 means that the style of leadership has a positive relationship to performance and gives the effect of 32.5 % . b.Partially a significant correlation between the performance of an employee incentive, where the hypothesis test showed that t = 4.171 > t table = 2.303. R = 0.484 and R2 = 0.234 meaning that incentives have a positive relationship to employee performance and give effect by 23.4 % . c.Partially a significant correlation between the work environment on employee performance, where the hypothesis test showed that t = 5.261 > t table = 2.303. R = 0.572 and R2 = 0.327 meaning that the work environment has a positive relationship to performance and gives the effect of 32. 7 % . d.Simultaneously, a significant correlation between the style of leadership, incentives, and the work environment on employee performance, where the hypothesis test shows that the calculated F = 28.500 > F table = 2, 776. Adjusted R = 0. 780 and R2 = 0.587 means that the style of leadership , incentives and the work environment has a positive and strong relationship to performance and effect of 58. 7 % .